An essential Saccharomyces cerevisiae gene homologous to SNF2 encodes a helicase-related protein in a new family. - Laurent, B C (1992)
The Saccharomyces cerevisiae SNF2 gene affects the expression of many diversely regulated genes and has been implicated in transcriptional activation. We report here the cloning and characterization of STH1, a gene that is homologous to SNF2. STH1 is essential for mitotic growth and is functionally distinct from SNF2. A bifunctional STH1-beta-galactosidase protein is located in the nucleus. The predicted 155,914-Da STH1 protein is 72% identical to SNF2 over 661 amino acids and 46% identical over another stretch of 66 amino acids. Both STH1 and SNF2 contain a putative nucleoside triphosphate-binding site and sequences resembling the consensus helicase motifs. The large region of homology shared by STH1 and SNF2 is conserved among other eukaryotic proteins, and STH1 and SNF2 appear to define a novel family of proteins related to helicases.